If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-x+9=6x-5
We simplify the equation to the form, which is simple to understand
-x+9=6x-5
We move all terms containing x to the left and all other terms to the right.
-1x-6x=-5-9
We simplify left and right side of the equation.
-7x=-14
We divide both sides of the equation by -7 to get x.
x=2
| 4y^4+9=13y^2 | | z-3.6=46.8 | | 2(x+3)=3(x+2) | | 3x-8=-7x+1 | | 3x-4yi=4+4i | | 2x^3=26 | | -2-16=3h-6 | | 2g-3=-19+g | | X+x+1=69 | | 2x+3=5-4x | | (x-7)(x+6)= | | 4x+20=12x+84 | | -2(4b+1)+(9b-6)=0 | | 8p-6-3p+2=15+2p+2 | | (-2x^3+4)(2x^2+5)= | | 13-10x=43-24x | | 3y-12=2(2y+44) | | (3x-3)(x-9)= | | 4(5+2)+2= | | 15x-28=-73 | | =-4x^2+5x-12 | | 7-1k=5+3k | | 18g+7=14g-9 | | 8x-12=3x+11 | | =4x^2-5x+12 | | 5a-8a+3a= | | -2d+18-4d=16 | | 2+3y=8 | | 3.3q-2.9-4.8q=2.5q-4.9 | | 6+b=7 | | 15d-8-3d=16 | | (2x^3+3x^2-1)=0 |